Perancangan Visual Branding OM Cuppu Barbershop di Gondangrejo Karanganyar - Umar Ilham Harttadi, Muhammad; Henny Lukitasari, Evelyne; Yulianto, Arif (Universitas Sahid Surakarta, 2023)
Abstract Om Cuppu Barbershop is a barbershop that provides barber services, offers various services, and sells various other products, namely pomade and hair tonic. The various virtue of Om Cuppu Barbershop is not enough to instil consumer loyalty to come, even though they are already well known in Gondangrejo. However, most people think that Om Cuppu barbershop is the same as other barbershops because most of the visitors come from the community base and the promotion method is still through word of mouth. The unique concept and virtue of Om Cuppu Barbershop can't be represented very well if the distribution is only spread by word of mouth without visualization that can attract people's attention to come. Based on the existing problems, the proper solution to promote Om Cuppu Barbershop is through Visual Branding Design as an effective and attractive promotional tool. This promotional media for Om Cuppu Barbershop aims to be able to attract more consumers to use the services of Om Cuppu Barbershop. The design of the visual branding of Om Cuppu Barbershop was carried out because there was no clear brand image, identity, and segmentation position in the minds of the public, so people became less interested in coming to use the cutting services of Om Cuppu Barbershop. Om Cuppu Barbershop's visual branding design uses SWOT analysis to get a visual brand that matches the character of Om Cuppu Barbershop. The visual branding design is done by creating a brand identity (colour, letter shape, graphic elements), changing the logo, and applying it to the media plan. It is hoped that this visual branding can create a comfortable and elegant image of Om Cuppu Barbershop in the minds of the people in Gondangrejo. The design method starts with thinking about ideas for design, surveying Om Cuppu Barbershop to take the required photos, conducting a brief by collecting data from observations, conducting brainstorming, which is an effort to develop ideas with consultation by the supervisor, and doing creative brief to produce a design that fits the background. Keywords: Om Cuppu Barbershop, Visual Branding, Brand, Image, Identity